A Less-Rare-Earth Permanent Magnet Machine with Hybrid Magnet Configuration for Electric Vehicles - Hui Yang; Peng Wu; Dabin Liu; Yuehan Zhu; Shuhua Fang; Heyun Lin (Energies, 2025)
This paper proposes a novel hybrid less-rare-earth permanent magnet (HLEPM) machine, which is designed to meet the demands of electric vehicle (EV) traction machines for high torque output and wide-speed-range high-efficiency performance. The designed machine features a unique hybrid permanent magnet arrangement, consisting of V-shaped rare-earth PMs and arc-shaped less-rare-earth PMs, respectively. The V-shaped rare-earth magnets can perform the flux-focusing effect well, not only enhancing the torque output capability but also improving the demagnetization with the standability of the arc-shaped less-rare-earth PMs during active short-circuit (ASC) conditions. First, the proposed machine is thoroughly designed and optimized to balance the torque capability and iron loss. Subsequently, the electromagnetic performance of the proposed HLEPM machine is evaluated using finite-element (FE) analysis and compared with that of a conventional double-layer V-shaped PMSM. Finally, the anti-demagnetization characteristics of the two machines under ASC conditions are analyzed in detail. The results validate the rationality and reliability of the proposed design.